The effect of teacher-guided peer feedback on English writing performance of Chinese EFL high school students - Zhang, Bo; Razali, Abu Bakar; Ismail, Lilliati (HRMARS, 2024)
Writing is an important output skill among the five basic skills of English, and giving and receiving feedback is an important aspect in the teaching and learning of writing. In the current English writing teaching in Chinese high schools, the method used is teacher feedback, but it is time-consuming and untimely, and it is not possible to give complete feedback on the mistakes and highlights of each student’s writing. This puts students in a state of passive acceptance, which is not conducive to learning autonomy, whereas peer feedback facilitates students’ independent learning through collaborative exchanges. Therefore, in the practical application of teaching, combining the two teaching methods can make up for each other’s deficiencies and work together to bring out better advantages. This study focuses on whether the combination of teacher feedback and peer feedback is effective in improving students’ writing performance as compared to the traditional teacher feedback particularly in three aspects of writing, which are idea/content, organization, and grammar. This study takes the process writing method and cooperative learning theory as the theoretical basis and selects two classes of the second year of high school in the first high school of Jixi City, Heilongjiang Province, as the experimental subjects for the teaching experiment. The control class used traditional teacher feedback and the experimental class used teacher-guided peer feedback. A pre- and post-writing test was used in this experiment to explore whether the students’ English writing improved or not, and the data were analyzed with the help of SPSS26. Finally, through data organization and analysis, this study found that compared with the traditional teacher feedback model, the combination of teacher feedback and peer feedback can effectively improve students’ writing performance, and the average scores on writing idea/content, organization, and grammar are all improved to a certain extent.